اثر البدو وقطاع الطرق على التجارة في بلاد الشام (1215ه ـ1337هـ /1800م ـ1918م) - البودي, مازن (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
تناول هذا البحث اهمية التجارة في بلاد الشام، من خلال الموقع الهام الذي انتج مدنا تجارية بارزة، وتطرق لمدى تأثير البدو سلبا وايجابا في حركة التجارة، وخطورتهم على حركة البضائع وسمعة الدولة. وأثر قطاع الطرق من خلال الضرر الذي يلحقونه بالتجارة مستغلين الطبيعة الجغرافية لبلاد الشام.This research deals with the importance of trade in the Levant, through the site, which produced the important commercial cities prominent, and displays the influence of Bedouin negatively and positively in the movement of trade and the danger to the movement of goods and the reputation of the state. And the impact of the road sector and the damage toll they trade, taking advantage of the geographical nature of the Levant.